Konsumsi Susu Kedelai Dengan Air Rebusan Kelor Terhadap Penurunan Dismenore Primer Pada Remaja Putri - Susmini, Susmini; Rosdiana, Yanti (Universitas Tribhuwana Tunggadewi, 2022)
A common health problem in adolescent girls is dysmenorrhea. Dysmenorrhea or also known as menstrual pain is one of the complaints that can be experienced by women during menstruation. The study's purpose was to determine the difference between the consumption of soy milk and boiled water of Moringa on primary dysmenorrhea in adolescents. The type of research used is quantitative research using a quasi experiment design with pre and post-tests without control. The purposive sampling method used recruited 19 participant who experienced primary dysmenorrhea on TlogoSurya Rt 02/Rw 02 street, Tlogomas, Malang city. The HARS instrument used for assess the pain scale. Data were analyzed using the independent t-test and paired t-test. Results showed a significant difference in the decrease of primary dysmenorrhea pain level after giving a combination of soy milk and Moringa boiled water in adolescent girls (p-value = 0.003), where there was a decreasing in primary dysmenorrhoea pain scale in the Moringa boiled water group. The study concluded that there was a significant difference in the decrease of the pain scale of primary dysmenorrhea after giving soy milk and Moringa boiled water. It also found that the decrease of the pain scale of primary dysmenorrhea was high in the group given Moringa boiled water.